Analysis of Factors Associated with the Risk of Hypertension in Aceh Embarkation Hajj Pilgrims - Nora Wirda; T. Maulana; Said Usman; M. Yani; Irwan Saputra (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Hypertension is one of the health problems, especially for hajj pilgrims, because hypertension is one of the entry points or risk factors for diseases such as heart disease, kidney failure, diabetes mellitus, and stroke. In 2024, cases of hajj pilgrims suffering from hypertension were 1,822 people (38.66%). This study aims to analyze the factors related to the incidence of hypertension in hajj pilgrims at the Aceh Embarkation. Quantitative research with a Cross Sectional Study approach using secondary data. The population is all hajj pilgrims at the Aceh Embarkation in 2024 totaling 4,713 people. The research sample is the total population. Bivariate data analysis with the chi-square test and multivariate with logistic regression. The results of the study obtained variables that have a significant relationship with hypertension are age (OR = 3.5; 95% CI: 3.08–3.95; p-value = 0.0001), family history (OR = 2; 95% CI: 1.74-2.25; p-value = 0.0001). Obesity (OR = 1.3; 95% CI: 1.14–1.44; p-value = 0.0001), diabetes (OR = 1.5; 95% CI: 1.28–1.75; p-value = 0.0001) and poor physical fitness OR = 1.7; 95% CI: 1.48–1.89; p-value = 0.0001). The conclusion of this study is that the age variable is the most dominant variable with the incidence of hypertension in the Aceh Embarkation Hajj pilgrims.